Cervical pap smear- A prospective study in a tertiary hospital (Journal of Pathology of Nepal, 2015)
Background: Cervical cancer is a leading cause of mortality and morbidity among women worldwide and most common gynaecological cancer in developing countries. Papanicolaou smear is a simple and cost effective screening test for cervical cancer. The aim of this study is to evaluate and interpret the cervical pap smear cytology in a tertiary hospital. The interpretation and reporting of the pap smear is based on 2001Bethesda system.Materials and methods: This is a prospective study conducted in a tertiary hospital, Nepal Medical College over a period of two and a half years (January 2013 to June 2015). All cervical pap smears received in the department of Pathology in the study period were included.Results: A total of 4160 cervical pap smears were reported in the study period. Majority of the cases were Negative for Intraepithelial lesion or malignancy (87.9%). Bacterial vaginosis, atrophy and reactive cellular changes associated with inflammation were seen in 5.3%, 2.4% and 1.5% cases respectively.   Epithelial cell abnormalities (0.5%) include Atypical squamous cells of undetermined significance, Low grade squamous intraepithelial lesion and High grade intraepithelial lesion. 88% of Low grade squamous intraepithelial lesion was seen in reproductive age group (20-45 years).Conclusion: Cervical cancer is the most common gynaecological cancer in the developing countries. Pap smear is the simple and cost effective screening tool to detect pre invasive cervical epithelial lesions.